The methodology of food design. Part 1. The individual aspect - A. Yu. Prosekov (Теория и практика переработки мяса, 2020)
Innovative technologies for food raw material processing and food production are becoming globally important within the framework of modern biotechnology. The need to create a universal methodology for food design and the importance of its implementation in different lines of human life activity are obvious. Within the paradigm of modern biotechnology, personalized diets that take into consideration the genetic characteristics of consumers are becoming more and more popular. Nutrition science deals with the development of this direction. It is divided into nutrigenetics and nutrigenomics. Nutrigenetics investigates an effect of modifications in genes on absorption of metabolites, nutrigenomics investigates how food components affect the work of genes. In this work, we consider mutations that influence the assimilation of metabolites and contribute to nutrigenetic research. The work is aimed at finding and studying genes responsible for eating behavior. Methods of analysis of genetic polymorphisms and modern achievements of nutrigenetics in the development of personalized nutrition are considered. The review allowed us to find and describe the genes that influenced human eating behavior: the role of genes, their localization, polymorphisms affecting the metabolism of nutrients and food preferences are indicated. Thirty four genes that influence eating behavior were identified, and significant shortcomings of current methods / programs for developing personalized diets were indicated. Weaknesses in the development of nutrigenetics were identified (inconsistency of data on SNP genes, ignoring population genetics data, information that is hard for consumers to understand, etc.). Taking into consideration all shortcomings, an approximate model for selecting a personalized diet is proposed. In the future, it is planned to develop the proposed model for making up individual diets.